Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
You need to isolate f.
[tex]\frac{f + 4}{g} = 6[/tex]
First, you need to multiply by g on both sides to "undo" the dividing by g on the left. You need to make sure you do the same thing to both sides to keep the equation equal.
[tex](\frac{f + 4}{g})*g = (6) * g \\ f + 4 = 6g[/tex]
Then, you need to subtract 4 from both sides to undo the addition of 4 to f on the left:
[tex](f + 4) - 4 = (6g) - 4 \\ f = 6g - 4[/tex]
And there you have it! f = 6g - 4. Hope this helps! :)
[tex]\frac{f + 4}{g} = 6[/tex]
First, you need to multiply by g on both sides to "undo" the dividing by g on the left. You need to make sure you do the same thing to both sides to keep the equation equal.
[tex](\frac{f + 4}{g})*g = (6) * g \\ f + 4 = 6g[/tex]
Then, you need to subtract 4 from both sides to undo the addition of 4 to f on the left:
[tex](f + 4) - 4 = (6g) - 4 \\ f = 6g - 4[/tex]
And there you have it! f = 6g - 4. Hope this helps! :)
We have two solutions for this problem based on the given equation.
Answer #1:
If the given equation was:
[tex] f + \frac{4}{g} = 6 [/tex]
To solve for f, we would need to isolate the "f" on one side of the equation.
In case of the above equation, we can simply do that by subtracting [tex] \frac{4}{g} [/tex] from both sides of the equation
This would give:
f + [tex] \frac{4}{g} [/tex] - [tex] \frac{4}{g} [/tex] = 6 - [tex] \frac{4}{g} [/tex]
f = 6 - [tex] \frac{4}{g} [/tex]
Answer #2:
If the given equation was:
[tex] \frac{f+4}{g} = 6 [/tex]
To solve for f, we would still need to isolate the "f" on one side of the equation.
This can be done as follows:
[tex] \frac{f+4}{g} = 6 [/tex] ................> multiply both sides by (g)
f + 4 = 6g ................> subtract 4 from both sides of the equation
f + 4 - 4 = 6g - 4
f = 6g - 4
Hope this helps :)
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.